2021
DOI: 10.3389/fpsyt.2021.695335
|View full text |Cite
|
Sign up to set email alerts
|

“This Is Something That Changed My Life”: A Qualitative Study of Patients' Experiences in a Clinical Trial of Ketamine Treatment for Alcohol Use Disorders

Abstract: Background: The therapeutic benefits of ketamine have been demonstrated for a variety of psychiatric disorders. However, the role of ketamine induced psychoactive experiences in mediating the therapeutic effects is unclear. Despite the growing quantitative research on the efficacy of ketamine treatment, very few studies examined participant experiences of ketamine infusions in a treatment setting.Aims: The current study aimed to examine participant experiences of ketamine infusions and how these relate to ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 53 publications
0
18
0
Order By: Relevance
“…Turning for the psychological experience in more detail, if we focus on the themes identified in psilocybin-assisted therapy for depression ( Watts et al, 2017 ) and search for them in the patient accounts of KAP for alcohol dependence ( Mollaahmetoglu et al, 2021 ), which is the controlled trial in which ketamine was embedded in a psychotherapeutic framework with more similarities to the PAP model, we are able to find some clear parallels. For example, in the first trial of psilocybin for depression, most patients reported how depression made them feel ‘trapped in their minds’, disconnected from themselves, their senses, others and the world and how psilocybin made them feel connected to their selves, senses, others, the world and to a spiritual principle ( Watts et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Turning for the psychological experience in more detail, if we focus on the themes identified in psilocybin-assisted therapy for depression ( Watts et al, 2017 ) and search for them in the patient accounts of KAP for alcohol dependence ( Mollaahmetoglu et al, 2021 ), which is the controlled trial in which ketamine was embedded in a psychotherapeutic framework with more similarities to the PAP model, we are able to find some clear parallels. For example, in the first trial of psilocybin for depression, most patients reported how depression made them feel ‘trapped in their minds’, disconnected from themselves, their senses, others and the world and how psilocybin made them feel connected to their selves, senses, others, the world and to a spiritual principle ( Watts et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…Results of qualitative interviews obtained during a RCT of KAP for alcohol dependence have also been published ( Mollaahmetoglu et al, 2021 ). Six key themes were identified: (1) multifaceted motivations to participate in the trial; (2) the influence of ‘set’ and ‘setting’ in the acute subjective experience; (3) the inherent contradictions of the ketamine experience; (4) rapidly fluctuating and changing experiences; (5) meaningful, spiritual and mystical experiences and (6) transformational effects of the infusions and the trial.…”
Section: Narrative Review Of Main Findings In Ketamine Studiesmentioning
confidence: 99%
“…Indeed, investigations show that conscious phenomenological changes appear not to be a necessary condition for the antidepressant response to ketamine (Ballard and Zarate, 2020 ). However, also ketamine-induced psychedelic experiences might be of additional therapeutic value, when used in a psychedelic-assisted psychotherapy context (Mathai et al, 2020 , 2022 ; Mollaahmetoglu et al, 2021 ; Dore et al, 2019 ).…”
Section: Mechanisms Of Actionmentioning
confidence: 99%
“…Ketamine can induce alterations in bodily perceptions, including feelings of lightness and floating [161,162]. Patients with AN tend to report high levels of cognitive control and cognitive rigidity [163,164].…”
Section: Neuropsychologymentioning
confidence: 99%
“…Additionally, disconnection from the self, others and the world is core to AN [168][169][170]. It is possible that ketamine may have an additional therapeutic impact for patients with AN by promoting flexibility, ego dissolution, detachment from one's internal dialogue and openness to experiences [162]. Moreover, the mystical and spiritual experiences that often manifest during ketamine treatment [162] may enable patients to connect with their spirituality and alter their perceptions of both themselves in the context of the wider world and of the universe itself.…”
Section: Neuropsychologymentioning
confidence: 99%